Structure Fabricated using Entry Level 3D Printer / Siti Nur Humaira Mazlan ...[et al.] - Mazlan, Siti Nur Humaira; Alkahari, Mohd Rizal; Ramli, Faiz Redza; Sudin, Mohd Nizam (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
3D printing or also known as additive manufacturing (AM) processes fabricate complex mechanical structures by using deposition of the filaments layer by layer technique. AM process has a good capability to fabricate the complex structure compares to conventional machining. However, there is limited design guideline for AM even for the most used AM technique which is fused deposition modeling technique (FDM). Thus, in this paper, various mechanical structures such as overhangs, bridges, wall thickness, hole diameter and vertical wire diameter were fabricated to study the manufacturability of the design structure fabricated by entry level 3D printer using polylactic acid (PLA) material. The parts manufactured were then measured to evaluate the dimensional accuracy and deviations between 3D computer-aided design (CAD) and nominal data. Based on the results, design guidelines for each respective mechanical structure have been recommended.